2002
DOI: 10.1016/s0014-5793(02)02830-2
|View full text |Cite
|
Sign up to set email alerts
|

The vitronectin binding area of plasminogen activator inhibitor‐1, mapped by mutagenesis and protection against an inactivating organochemical ligand

Abstract: A distinguishing feature of serpins is their ability to undergo a conformational change consisting in insertion of the reactive centre loop (RCL) into L L-sheet A. In the serpin plasminogen activator inhibitor-1 (PAI-1), RCL movements are regulated by vitronectin, having a previously poorly defined binding site lateral to PAI-1's L L-sheet A. Using a novel strategy, based on identification of amino acid residues necessary for vitronectin protection of PAI-1 against inactivation by 4,4P Pdianilino-1,1P P-bisnap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 22 publications
6
73
0
Order By: Relevance
“…For example, in the context of cell adhesion, SerpinE1 competes with uPAR and integrins for vitronectin binding (10,37,38), but SerpinB2 does not bind vitronectin (39). Importantly, the vitronectin-binding site(s) in SerpinE1 are distinct from the LDLR minimal binding motif (40), and the SerpinB2 constructs used in this study did not bind to vitronectin or impact on cell adhesion (data not shown). This excludes any influence of modulation of cell adhesion on the proliferative effects of SerpinB2 YK on a VLDLR-dependent cell line and implies that these effects are a direct response of the increased affinity for VLDLR.…”
Section: Discussionmentioning
confidence: 83%
“…For example, in the context of cell adhesion, SerpinE1 competes with uPAR and integrins for vitronectin binding (10,37,38), but SerpinB2 does not bind vitronectin (39). Importantly, the vitronectin-binding site(s) in SerpinE1 are distinct from the LDLR minimal binding motif (40), and the SerpinB2 constructs used in this study did not bind to vitronectin or impact on cell adhesion (data not shown). This excludes any influence of modulation of cell adhesion on the proliferative effects of SerpinB2 YK on a VLDLR-dependent cell line and implies that these effects are a direct response of the increased affinity for VLDLR.…”
Section: Discussionmentioning
confidence: 83%
“…A recombinant form of vitronectin lacking the somatomedin B domain (r⌬sBVN) was expressed in the baculovirus FastBac system and purified as described (32). PAI-1 was produced according to the method outlined by Jensen et al (21). The numbering used to denote the amino acid positions in PAI-1 throughout the present work is Ser-1-Ala-2-Val-3-His-4 -His-5, according to Andreasen et al (35).…”
Section: Methodsmentioning
confidence: 99%
“…The binding site for the SMB domain on PAI-1 has been well defined by x-ray crystallography (15, 31) and site-directed mutagenesis (19,21). Because the mutants identified in this study (K82E, R117E/ R120E, R103A/M112A/Q125A, K71A/R78A, Y81A/K82A, and W177F) interact in the latent form at a site that is separate from the recognition sequences for the SMB domain, it was important to complete our analysis and test for any effects of these mutagenized forms of PAI-1 in their active conformation on binding to full-length vitronectin, which contains the SMB domain.…”
Section: Comparison Of the Binding Of Active And Latent Forms Of Pai-mentioning
confidence: 99%
“…Multimeric vitronectin was prepared by denaturation of the protein in 8 M urea for 2 h at room temperature followed by dialysis into PBS (140 mM NaCl, 3 mM KCl, 10 mM Na 2 HPO 4 , 2 mM KH 2 PO 4 , pH 7.4). Recombinant human wild-type PAI-1 and recombinant stable PAI-1 mutant, 14-1B (38), used in the ELISA assays were both purchased from Molecular Innovations, Inc. PAI-1 used in the Biacore experiments and latency transition assays was produced according to the method outlined in Jensen et al (28). The PAI-1 protein preparations were tested for activity using a urokinase inhibition assay; all behaved similarly and fully inhibited urokinase.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, the complementary vitronectin binding site within PAI-1 has been thoroughly investigated. A region between helices D, E, and F in PAI-1 termed the flexible joint region was proposed to comprise the primary binding site for vitronectin by Lawrence et al (27) in 1994 and was finally fully mapped to this region by Jensen et al (28) in 2002. The epitope was later confirmed by x-ray crystallography studies of the PAI-1-somatomedin B complex (9).…”
mentioning
confidence: 99%